Beliefs about medicines’ association with endocrine therapy adherence in early breast cancer survivors in Croatia - Okroša Ana Dugonjić; Silovski Tajana; Plavetić Natalija Dedić; Silovski Hrvoje; Kovačić Ana; Mucalo Iva (Acta Pharmaceutica)
This observational, cross-sectional study conducted at the University Hospital Centre Zagreb (UHC Zagreb) aimed to explore patients’ beliefs about adjuvant endocrine therapy (AET) as well as their association with non-adherence and sociodemographic and clinical factors. Out of 420 early breast cancer (BC) patients included in the study, 79.5 % perceived AET necessary and important for their health, as measured by the Belief About Medicines Questionnaire (BMQ), with the mean necessity score (20.4 ± 3.68) significantly higher than the mean concerns score (13 ± 4.81) (p < 0.001). Based on the Medication Adherence Report Scale (MARS-5), 44.4 % (n = 182) of the participants were non-adherers, out of which 63.2 % (n = 115) were unintentional and 36.8 % (n = 67) intentional non-adherers. Significantly higher concern beliefs were found among patients that were younger (p < 0.001), employed (p < 0.001), intentionally non-adherent to AET (p = 0.006), had a lower body-mass index (p = 0.005) and a higher level of education (p < 0.001), were premenopausal at the time of diagnosis (p < 0.001), taking tamoxifen treatment (p = 0.05) and receiving ovarian suppression (p < 0.001). Younger patients should be recognized as being at risk of non-adherence as they hold greater concern beliefs about medicines.